2020
DOI: 10.1038/s41586-020-2712-z
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable haemodynamic endothelial cells for organogenesis and tumorigenesis

Abstract: Endothelial cells adopt tissue-specific characteristics to instruct organ development and regeneration 1,2. This adaptability is lost in cultured adult endothelial cells, which do not vascularize tissues in an organotypic manner. Here, we show that transient reactivation of the embryonic-restricted ETS variant transcription factor 2 (ETV2) 3 in mature human endothelial cells cultured in a serum-free three-dimensional matrix composed of a mixture of laminin, entactin and type-IV collagen (LEC matrix) 'resets' t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(131 citation statements)
references
References 49 publications
0
131
0
Order By: Relevance
“…Endothelial progenitor cells (EPC) harvested as endothelial colony-forming cells (ECFC) from cord blood can also be used, but those from adult peripheral blood exhibit limited proliferation potential (Ferratge et al, 2017). Recently, Palikuqi et al (2020) reported "reset" vascular EC that transiently express ETS variant transcription factor 2 (ETV2) and that self-assemble into vascular networks and arborized cancerous human colon organoids. Quite remarkably, only cells from human origin are used in relevant 3D models; while isolation and culture of mouse EC have been developed for years now, their ability to form capillaries has proven to be more challenging (Nowak-Sliwinska et al, 2018).…”
Section: Endothelial Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endothelial progenitor cells (EPC) harvested as endothelial colony-forming cells (ECFC) from cord blood can also be used, but those from adult peripheral blood exhibit limited proliferation potential (Ferratge et al, 2017). Recently, Palikuqi et al (2020) reported "reset" vascular EC that transiently express ETS variant transcription factor 2 (ETV2) and that self-assemble into vascular networks and arborized cancerous human colon organoids. Quite remarkably, only cells from human origin are used in relevant 3D models; while isolation and culture of mouse EC have been developed for years now, their ability to form capillaries has proven to be more challenging (Nowak-Sliwinska et al, 2018).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Quite remarkably, using mixtures of Matrigel TM with natural polymers like fibrin turned out to noticeably improve capillary formation and resulted in efficient inosculation with the host vasculature and further blood perfusion after implantation in mice (Laib et al, 2009). Recently, Palikuqi et al (2020) developed matrices made of mixture of laminin, entactin, and collagen IV that support vasculogenesis.…”
Section: Natural Polymers For Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in such approaches, endothelial cells may not always be free to interact with tumor cells because of the artificial membranes used in the organ-on-a-chip devices. To address this issue, endothelial cells were modified to produce 'reset' vascular endothelial cells (R-VECs) that grew into 3D branching vessels capable of transporting human blood in microfluidic chambers and when transplanted into mice (Palikuqi et al, 2020). These R-VECs adapted their growth upon their coculture with either normal colon organoids or patient-derived colorectal organoids.…”
Section: Angiogenesis and Cancer Cell Intravasationmentioning
confidence: 99%
“…In organoids and tumoroids, complicated structures of organs and tumors can be reconstructed in vitro. For example, tumor microenvironment such as vasculatures [16,17], immune cells [12], fibroblastic stromal cells, and normal epithelial cells can be reconstructed in vitro within organoids and tumoroids [18][19][20]; (6) Gene expression signatures, molecular profiles, and secretory phenotypes are particular in 3D tumoroids according to their physical properties, e.g., moonlighting metalloproteinases (MMPs) [6,13,[21][22][23], ATP-binding cassette (ABC) transporters including ABC-G1 and ABC-G2 [15], and intercellular adhesion molecules such as EpCAM/CD326 and E-cadherin [7,12], stem cell markers such as CD44 variants and CD133 [7], other factors potentially involving stemness such as ESRP1/2, MUC1, and Notch/delta signal [7]. The molecular profiles of tumoroids involve properties of CSCs [7].…”
Section: Introductionmentioning
confidence: 99%